Development of INSVAGRAM: An English Subject-Verb Agreement Mobile Learning Application - John Paul Palo Miranda (Kassel University Press, 2021)
English language proficiency of students in the Philippines is a point of concern by many institutions particularly as it was highlighted when the results of the first participation of the country in the Program for International Student Assessment (PISA) was released. The use of technology-aided educational applications dedicated to language learning, particularly those that can be accessed through mobile devices, is heavily studied internationally. However, in the Philippines, there is a limited number of developed mobile-supported applications that assist acquisition and learning of language, specifically English. Thus, the study aims were to develop a mobile learning application intended to assist students in learning a least mastered topic in English. The study utilized mixed-method descriptive research design. For the quantitative part, it employed a content-validated questionnaire to survey 132 fifth grade students, while for the qualitative part; it interviewed five English language teachers in the Philippines. A mobile learning application intended for smartphones in an Android OS was developed with focus on subject-verb agreement (SVA) as identified topic which was divided into 10 sub-topics. The application comprises two main parts: The Learn and Play Mode. Additionally, the application was also able to integrate an animated character named Alvin to simulate interaction. Alvin interacts with the user by narrating lessons, giving remarks, providing basic corrective feedback in the form of text, and expressing feelings based on the user’s inputs when doing exercises. The survey from students aged 10 to 12 years old showed that they have very often access to technological devices (i.e., desktop, laptops, tablet, smartphone) (M = 4.33) and that their technology aptitude in using them is high (M = 3.45). Furthermore, results also showed that students mostly prefer smartphones for their learning as it is their most available device at home. It is recommended to subject the developed mobile application to a user acceptance and usability testing in different educational contexts. Additionally, it is suggested to explore newer technologies like artificial intelligence to make the application intelligent and more responsive to students’ needs and inputs. Future studies may also include addition of new topics as well as developing similar applications that are localized and culturally-aware.